Peningkatan Peran Pemanfaatan Pekarangan dan Kader Posyandu dalam Membantu Penurunan Masalah Gizi Terutama Stunting Balita di Desa Krisik (Kecamatan Gandusari, Kabupaten Blitar) - Saati, Elfi Anis; Andriawan, Sony; Indratmi, Dian; Harini, Ririn (JAST : Jurnal Aplikasi Sains dan Teknologi, 2024)
There are 67 out of 340 toddlers will experience stunting in 2022 in Krisik village, Gandusari subdistrict, Blitar district. This service aims to reduce cases of stunting through activities: Education about balanced nutrition for families; Assistance in the use of aquaponic-based Sustainable Food Houses/RPL in the yard; Training on the creation of healthy food processing to meet the nutritional needs of toddlers and families and support family food security. Activity stages: 1) Survey of village potential locations and nutritional problems, especially stunting; 2) Survey of potential locations for land use of yards; 3) Socialization activities for stunting solutions in Krisik village; 4) BIMTEK on the creation of processed food, use of yards or RPL (Sustainable food home). ). The results of the activity were an increase in nutritional knowledge, healthy food for stunting solutions, the importance of balanced nutrition in children's growth, and Posyandu cadre mothers were able to adopt BIMTEK for healthy food creations, namely fruit/vegetable jelly (dragon fruit skin), flowers (roses), and Pigmented vegetable nuggets (spinach/mustard greens) as a natural coloring are high in antioxidants. This program has been proven to help reduce the stunting of toddlers in Krisik-Blitar village by around 15 percent. The results of the food creation training have become PMT products when the monthly Village Posyandu takes place. The trained Posyandu cadres take part in a menu competition for stunted toddlers. Utilizing the yard through the RPL application can help change people's behavior in meeting the nutritional needs of families, especially children, by providing healthy, nutritious food and maintaining their family's food security. ABSTRAKTerdapat 67 dari 340 balita yang mengalami stunting pada tahun 2022 di desa Krisik, kecamatan Gandusari, kabupaten Blitar. Pengabdian ini bertujuan mengurangi kasus stunting melalui kegiatan: 1) Edukasi tentang gizi seimbang kepada keluarga, 2) Pendampingan pemanfaatan Rumah Pangan Lestari/RPL berbasis akuaponik di pekarangan, 3) Pelatihan kreasi pengolahan pangan sehat bagi pemenuhan kebutuhan gizi balita dan keluarga, serta mendukung ketahanan pangan keluarga. Tahapan kegiatan: 1) Survey lokasi potensi desa dan permasalahan gizi terutama stunting, 2) Survey lokasi potensi lahan pemanfaatan pekarangan, 3) Kegiatan sosialisasi solusi stunting di desa Krisik, 4) BIMTEK kreasi pangan hasil olahan, pemanfaatan pekarangan atau RPL (Rumah pangan lestari). Hasil kegiatan terdapat peningkatan pengetahuan gizi, pangan sehat bagi solusi stunting, pentingnya gizi seimbang dalam pertumbuhan anak, serta Ibu-ibu kader Posyandu dapat mengadopsi BIMTEK kreasi pangan sehat, yaitu jelly buah/sayuran (kulit buah naga), bebungaan (mawar), dan nuget sayuran (bayam/sawi) berpigmen sebagai perwarna alami tinggi antioksidan. Program ini terbukti membantu menurunkan stunting balita di desa Krisik-Blitar sekitar 15 persen. Hasil pelatihan kreasi pangan sudah menjadi produk PMT saat Posyandu Desa bulanan berlangsung, Kader Posyandu binaan ikut lomba menu bagi Balita stunting. Memanfaatkan pekarangan melalui aplikasi RPL dapat membantu mengubah perilaku masyarakat dalam memenuhi kebutuhan gizi keluarga terutama anak, melalui penyediaan makanan sehat bergizi dan menjaga ketahanan pangan keluarganya